Pengaruh Struktur Kepemilikan Institusional, Keputusan Pendanaan Dan Kebijakan Hutang Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2019 (Studi kasus terhadap Perusahaan Manufaktur Sektor Proprti Real Estate & Konstruksi dan Keuangan) - M. Umar Izzul Chaq; Ronny Malavia Mardani; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine the effect of institutional ownership, funding decisions and debt policies on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2019 (Case study of manufacturing companies in the real estate & construction and financial property sectors). This sampling method was purposive sampling and obtained 49 samples that met the criteria from 170 companies that were observed. Technical analysis of this research data is descriptive statistics. The results of this study indicate that the influence of institutional ownership structure as measured by the number of shares of institutional parties divided by total outstanding shares, funding decisions are measured by LDR (Long Term To Debt Ratio) and debt policy is measured by DER (Debt To Equity Ratio) shows that there is no significant effect on firm value as measured by PBV (Price Book Value). Keywords : Institutional Ownership, Funding Decisions, Debt Policies